2013
DOI: 10.1186/2190-4715-25-4
|View full text |Cite
|
Sign up to set email alerts
|

Proposal for environmental mixture risk assessment in the context of the biocidal product authorization in the EU

Abstract: Background: The EU Council and Parliament recently agreed on a new regulation that will implement a new EU-wide, harmonized system for the authorization for biocidal products. Such products are in most cases multi-component mixtures of one or more active substances plus a range of co-formulants that serve different purposes, e.g. as stabilizers or preservatives. They are only allowed on the European market if their intended use does not lead to unacceptable risks for the environment. Consequently, the assessme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 17 publications
0
20
0
Order By: Relevance
“…While the prediction–observation comparisons based on EC10 values carried higher reliability because of available and reasonably tight confidence intervals, MDRs derived from NOEC values resulted in similar conclusions despite the inherent problem of assuming (incorrectly) identical effect levels for the used NOEC values. The 2 examples of mixtures assessed in a chronic test provided some evidence that the usage of NOEC instead of ECx values as suggested for pragmatic reasons does not introduce much greater error.…”
Section: Discussionmentioning
confidence: 97%
“…While the prediction–observation comparisons based on EC10 values carried higher reliability because of available and reasonably tight confidence intervals, MDRs derived from NOEC values resulted in similar conclusions despite the inherent problem of assuming (incorrectly) identical effect levels for the used NOEC values. The 2 examples of mixtures assessed in a chronic test provided some evidence that the usage of NOEC instead of ECx values as suggested for pragmatic reasons does not introduce much greater error.…”
Section: Discussionmentioning
confidence: 97%
“…However, at such low doses, the interpretation of data is tricky and controversial, as illustrated by the conclusions derived by different groups of experts (Kortenkamp et al, 2009; SCCS, SCHER, SCENIHR, 2011) from a study with fish (Hermens et al, 1985), two studies with algae (Walter et al, 2002;Faust et al, 2003), and one study using an in vitro cellular test (Payne et al, 2001). Synergistic interactions have been documented for pesticides considering both biocidal products (Bjergager et al, 2011;Backhaus et al, 2013) and mixtures commonly detected in aquatic habitats (Laetz et al, 2009). They include toxicokinetic, metabolic, and toxicodynamic interactions.…”
Section: Emerging Concern With Legacy Pollutants and Emerging Contamimentioning
confidence: 99%
“…Furthermore, even for heterogeneous mixtures with similarly and dissimilarly acting substances, the predictions with CA and IA give an adequate range of the mixture toxicity, within which observed effects are found . CA is often proposed as ‘worst case’ for assessing the mixture effects of co‐occurring substances, because it usually gives predictions of mixture toxicity higher than IA. Therefore, despite the simplicity of the mixture models described, and the difficulty of fulfilling the assumptions the make, for example, by being certain that the mode of action between the substances is strictly similar or strictly dissimilar, these models are now largely adopted to predict mixture effects of multiple compounds.…”
Section: Accuracy Of the Ca And Ia Modelsmentioning
confidence: 99%
“…Furthermore, CA provides good to excellent predictions of the observed mixture toxicity for many studies, within a small range of deviation (observed toxicity rarely exceeding predictions by a factor of 2), even regardless of the mode of action of substances in the mixture, i.e., when CA is applied with substances having dissimilar modes of action. This range can be used as a security factor for the mixture effect predictions that may account for potential synergistic interactions . Therefore, CA is often recommended as the default precautionary model as mentioned above.…”
Section: Accuracy Of the Ca And Ia Modelsmentioning
confidence: 99%
See 1 more Smart Citation